Graft rejection episodes after Descemet stripping with endothelial keratoplasty: part two: the statistical analysis of probability and risk factors. Issue 3 (19th November 2008) - Price, M O; Jordan, C S; Moore, G; Price, F W
Abstract : Aim: To investigate risk factors and probability of initial immunological graft rejection episodes after Descemet stripping with endothelial keratoplasty (DSEK). Methods: Outcomes of 598 DSEK cases from a single tertiary referral centre were reviewed. Risk factors and probability of rejection were assessed by multivariate Cox proportional hazards modelling. Results: Rejection episodes occurred in 54 eyes of 48 patients. Estimated probability of a rejection episode was 7.6% by 1 year and 12% by 2 years after grafting. Relative risk of rejection was five times higher for African–American patients compared with Caucasians (p = 0.0002). Eyes with pre-existing glaucoma (9%) or steroid-responsive ocular hypertension (27%) had twice the relative risk of rejection (p = 0.045) compared with eyes that did not have those problems. Patient age, sex and corneal diagnosis did not significantly influence rejection risk. Risk of rejection was not increased when fellow eyes were grafted within 1 year of the first eye (p = 0.62). Conclusions: Pre-existing glaucoma or steroid-responsive ocular hypertension and race were the two factors that independently influenced relative risk of rejection after DSEK. Rejection risk was not increased if the fellow eye was grafted within the prior year with DSEK.